Brief Report: No Differences Between Lopinavir/Ritonavir and Nonnucleoside Reverse Transcriptase Inhibitor–Based Antiretroviral Therapy on Clearance of Plasmodium falciparum Subclinical Parasitemia in Adults Living With HIV Starting Treatment (A5297). (1st February 2022) - Shaffer, Douglas; Kumwenda, Johnstone; Chen, Huichao; Akelo, Victor; Angira, Francis; Kosgei, Josphat; Tonui, Ronald; Ssali, Francis; McKhann, Ashley; Hogg, Evelyn; Stewart, V. Ann; Murphy, Sean C.; et al.
Abstract : Background: HIV protease inhibitors anti- Plasmodium falciparum activity in adults remains uncertain. Methods: Adults with HIV CD4+ counts >200 cells/mm3 starting antiretroviral therapy (ART) with P. falciparum subclinical parasitemia ( Pf SCP) were randomized 1:1 to (step 1) protease inhibitor lopinavir/ritonavir (LPV/r)-based (arm A) or nonnucleoside reverse transcriptase inhibitor (nNRTI)-based ART (arm B) for 15 days. In step 2, participants received nNRTI-based ART and trimethoprim/sulfamethoxazole prophylaxis for 15 days. P. falciparum SCP clearance was measured by polymerase chain reaction. The Fisher exact test [95% exact confidence interval (CI)] was used to compare proportions of P. falciparum SCP clearance (<10 parasites/μL on 3 occasions within 24 hours) between LPV/r and nNRTI arms at day 15. The Kaplan–Meier method and log-rank test were used to compare time-to-clearance. Results: Fifty-two adults from Kenya, Malawi, and Uganda with a median age = 31 (Q1, Q3: 24–39) years, 33% women, with baseline median CD4 + counts of 324 (259–404) cells/mm 3, median HIV-1 RNA viremia of 5.18 log10 copies/mL (4.60–5.71), and median estimated P. falciparum density of 454 parasites/μL (83–2219) enrolled in the study. Forty-nine (94%) participants completed the study. At day 15, there was no statistically significant difference in the proportions of P. falciparum SCP clearance between the LPV/r (23.1% clearance; 6 of the 26) and nNRTI (26.9% clearance; 7 of the 26) arms [between-arm difference 3.9% (95% CI, −21.1% to 28.4%; P = 1.00)]. No significant difference in time-to-clearance was observed between the arms ( P = 0.80). Conclusions: In a small randomized study of adults starting ART with P. falciparum SCP, no statistically significant differences were seen between LPV/r- and nNRTI-based ART in P. falciparum SCP clearance after 15 days of treatment.